HUBUNGAN HbA1c PADA PASIEN DIABETES MELITUS TIPE 2 DENGAN OBESITAS DAN TANPA OBESITASDI RSUD DR. PIRNGADI KOTA MEDAN - Sagala, Daniela; Nainggolan , , Renatha N; Sinurat, Suryati (Jurnal Kedokteran Methodist, 2022)
Background: Diabetes mellitus is a collection of metabolic diseases caused by impaired insulin secretion, insulin action, or both so that it has the characteristics of hyperglycemia. In patients with type 2 diabetes with obesity, there can be an increase in fatty acids or Free Fatty Acid in cells. Increased will cause a decrease in glucose delivery to the plasma membrane, resulting in insulin resistance in muscle and adipose tissue Objective: To determine the relationship between HbA1c in Type 2 Diabetes Patients with Obesity and Without Obesity in Dr. Hospital. Pirngadi Medan City Methods: This research was conducted by analytical observation with an approach using a cross sectional design that is only temporary or to see the relationship between HbA1c in Type-2 Diabetes Patients with Obesity and Without Obesity. Pirngadi Medan City. Total sampling technique is a sampling method where all samples are taken and meet the inclusion and exclusion criteria. Results: From the results of this study, there is a relationship between HbA1c in Type-2 Diabetes Patients with Obesity and Without Obesity in Dr. Hospital. Pirngadi Medan City (p=0.01). Conclusion: The occurrence of excessive fat accumulation in the body of obese patients can lead to insulin resistance which affects blood sugar levels which causes diabetes mellitus.